Work correlates of back problems and activity restriction due to musculoskeletal disorders in the Canadian national population health survey (NPHS) 1994–5 data. Issue 11 (1st November 2001) - Cole, D C; Ibrahim, S A; Shannon, H S; Scott, F; Eyles, J
Abstract : OBJECTIVES: To describe the prevalence of musculoskeletal problems in the Canadian working population and to determine cross sectional associations between such problems and work factors, particularly job strain and physical demand variables. METHODS: The Canadian 1994 national population health survey (NPHS) sampled 4230 working men and 4043 working women (ages 18–64) who answered an abbreviated version of the job content questionnaire. Workers were classified into four strain categories: high, passive, active, and low. Outcomes were restricted activity due to musculoskeletal disorders and the diagnosis of a back problem (both yes or no). Survey weights were incorporated to allow for different probabilities of selection. Logistic regression analyses were carried out separately for women and men, controlling for sociodemographic factors. RESULTS: Prevalence of chronic back problems diagnosed by a health practitioner was 14.5% among men and 12.5% among women. Men had a 6.6% prevalence of restricted activity due to musculoskeletal disorders, whereas the corresponding figure for women was 5.3%. Women, but not men, in high strain jobs were more likely to report both back problems (odds ratio (OR) 1.60, 95% confidence interval (95% CI) 1.14 to 2.28) and restricted activity (OR 1.98, 95% CI 1.16 to 3.48) compared with those in low strain jobs. High physical exertion was an independent predictor of back problems in both sexes. For both men and women, low social support at work and high job insecurity were independent predictors of restricted activity due to musculoskeletal disorders. Conversely, chronic back problems contributed to explanation of high job strain among women (OR 1.76, 95% CI 1.30 to 2.39) and high physical exertion among men (OR 1.39, 95% CI 1.09 to 1.77), whereas restricted activity due to musculoskeletal disorders contributed to explanation of high job insecurity in both sexes. CONCLUSIONS: Associations of interest between work stressors and musculoskeletal problems in this cross sectional study provide evidence for physical and psychosocial factors both affecting disability and being affected by disability in a working population.